Saúde pública versus saúde privada: lutas e resistência da frente nacional contra a privatização da saúde - Martins, Sarah Silva (2022)
This dissertation analyzes the actions and resistances of the National Front Against the Privatization of Health (FNCPS), in the socio-historical particularities of capitalism in Brazil, apprehending the determinants that tension the continuity of the fight and defense for universal and quality public health. The investigation developed and that integrates the dissertation enabled the researcher to study the strategies of struggles of the FNCPS in a conjuncture of extreme attack of the capital to the historical social conquests of the working class. The guiding hypothesis of the research is that the strengthening and defense of the SUS contains in the National Front Against Health Privatization (FNCPS) a field of resistance to neoliberal and neoconservative attacks against the working class, ordered by the expansion and intensification of the exploitation of the workforce by the capital. The research methodology was bibliographic and documentary. In this perspective, based on inventoried documentary sources, the agenda, the strategic actions of the National Front against the Privatization of Health are related to the political and social Project of the Brazilian Sanitary Reform that originates and sustains the principles and guidelines of the Unified Health System (SUS); the positions and resistance manifested by the FNCPS against the privatization of public health and the reallocation of public funds to the detriment of social policies, through outsourcing and flexibility, are apprehended. This study, developed in the Masters in Social Work at PUC Goiás, focuses on the resistance and defense of the constitutional SUS, with a view to contributing to the strengthening of the SUS and the constitution of a new sociability